A ±0.48°C (3σ) Inaccuracy BJT-Based Temperature Sensor With 241 μs Conversion Time for Display Driver IC in 40 nm CMOS - Yong-Sung Ahn; Jeong-Mi Park; Jin-Ku Kang; Jaehoon Jun (IEEE Access, 2023)
This paper describes a fast BJT-based temperature sensor with ±0.48°C inaccuracy embedded in a display driver integrated circuit (DDIC) for detecting the temperature of a display module. It utilizes the base-emitter voltage difference between two BJT elements in a bandgap reference (BGR) circuit to create a voltage proportional to the absolute temperature, which is then converted to a digital value through an analog-to-digital converter (ADC). The voltage varies proportionally with the temperature change obtained from the temperature sensor and is directly digitized without removing the offset errors from the analog circuit stage. The error is mitigated through a proposed digital correction method. The proposed on-chip temperature sensing circuit for sophisticated DDIC applications shows an inaccuracy of ±0.48°C and a resolution of 0.25°C by applying a digital compensation method including thermal resistance calibration considering an operation mode of a display. The conversion time of the temperature to digital converter is only $241 ~μ \text{s}$ . The prototype dissipates only $129.17 ~μ \text{W}$ and achieves high energy-efficiency of 31.1 nJ/conversion.